TOWARD EFFECTIVE OF ASEAN MUTUAL LEGAL ASSISTANCE IN COMBATING NON TRADITIONAL SECURITY THREATS IN SOUTHEAST ASIA REGION - Syafrinaldi, Syafrinaldi; Prayuda, Rendi; Harto, Syafri (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2023)
The issue of non traditional security is currently one of the changes in studies in international security. One of the changes is from state security to human security. A form of real threat to human security is transnational crime. Therefore, in dealing with transnational crime, coordination between law enforcers in each country is needed by implementing international law. This article uses the approach of liberalism with a qualitative descriptive research approach (literature study) The research findings explain that the lack of domestic law enforcement in ASEAN countries causes transnational criminals to break away from domestic law and flee to other countries, causing fears of new threats in the country where the refugees are fleeing. In essence, there is no country that is able to stand on its own to resolve this transnational crime case. Therefore, multilateral cooperation between countries is needed. ASEAN, which in this case is a Southeast Asian multilateral institution must regulate strategies through MLA (Mutual Legal Assistance in criminal matters).